2009
DOI: 10.1016/j.geoderma.2009.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Natural radioactivity levels (K, Th, U and Rn) in the Cecita Lake area (Sila Massif, Calabria, Southern Italy): An attempt to discover correlations with soil features on a statistical base

Abstract: Soils can exhibit a complex range of physical, mineralogical, and chemical features depending on many interrelated factors such as parental rock composition and mineralogy, climate, topography, vegetation amounts and types, water infiltration versus runoff, soil moisture, organic matter, presence and types of anthropogenic contaminants, and many others. Radioactivity as measured on these complex systems is consequently perturbed by several mixed effects. In order to find out a possible (potential) relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…8 Buccianti et al (2009) and Belivermis et al (2010) confirmed the influence of particle size on radionuclide specific activities in soil. 9,10 Nevertheless, there is a scarcity of information on the behaviour of radionuclides in the soils of Serbia. 11,12 In this study the depth distribution of the natural radionuclides, 40 K, 226 Ra and 232 Th, and Chernobyl-derived 137 Cs, was studied in profiles representing typical soil types of the Belgrade area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Buccianti et al (2009) and Belivermis et al (2010) confirmed the influence of particle size on radionuclide specific activities in soil. 9,10 Nevertheless, there is a scarcity of information on the behaviour of radionuclides in the soils of Serbia. 11,12 In this study the depth distribution of the natural radionuclides, 40 K, 226 Ra and 232 Th, and Chernobyl-derived 137 Cs, was studied in profiles representing typical soil types of the Belgrade area.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 In this study the depth distribution of the natural radionuclides, 40 K, 226 Ra and 232 Th, and Chernobyl-derived 137 Cs, was studied in profiles representing typical soil types of the Belgrade area. 13 Although a substantial body of knowledge already exists in this area, in the majority of studies correlations between natural or anthropogenic radionuclides and a limited number of soil parameters, mainly particle size, [6][7][8][9][10][14][15][16][17][18][19][20][21][22] pH, organic matter content, 6,10,[16][17][18][20][21][22] carbonate content 6,7,16 or selected stable elements, 7,20,21 have been investigated. To assess the pedogenic effect on the distribution of radionuclides, the relationships between radionuclide specific activities and a number of soil properties (particle size distribution, pH, organic matter content, carbonate content, cation exchange capacity, bulk density, particle density, saturated hydraulic conductivity and specific electrical conductivity) were analysed.…”
Section: Introductionmentioning
confidence: 99%
“…However, locations with low U/Th indicate that processes responsible for U-enrichment are higher than that of [44]. Furthermore, it is also possible that weathering and other soil-forming processes might have caused the depletion of U from the rocks in some locations, leading to their uneven spatial distribution [49].…”
Section: Radionuclide Concentrations and Distributions Patternmentioning
confidence: 99%
“…Furthermore they can well describe processes of element partition, or groups of elements, when they present coherent (similar) behaviour in geochemistry (Buccianti, 2011a;Buccianti, 2011b). The identification of easily interpretable balances may also be useful to reveal natural laws governing proportions in several field of earth (Buccianti and Esposito, 2004;Nisi et al, 2008;Buccianti et al, 2009) and ecological sciences (Bertocchi et al, 2008;Tricarico et al, 2008). Although the sequential binary partition can be performed following rigorous mathematical steps (Egozcue et al, 2003, Hron et al, 2010, here in the case studies analysed, the choice of the balances starts from a geochemical hypothesis.…”
Section: Working On Coordinates: the Ilr Transformation Of Compositiomentioning
confidence: 99%